2014
DOI: 10.2478/jppr-2014-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Ozone Concentrations and Short Exposure Times on the Mortality of Immature Stages of the Indian Meal Moth, Plodia Interpunctella (Lepidoptera: Pyralidae)

Abstract: Abstract:In Iran, the Indian meal moth, Plodia interpunctella (Hübner), is one of the most important pests of such stored products as date fruits and pistachio nuts. Ozone was applied as a gas at four concentrations (0, 2, 3, and 5 ppm) for four different periods (30, 60, 90, and 120 min) on the immature stages of P. interpunctella. The results indicated that by increasing the concentration and exposure time, the rate of mortality increased for all tested stages. This study showed that 12-day-old larvae were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Similarly, Isikber and Oztekin (2009) investigated the susceptibility of Tribolium confusum Jacquelin du Val life stages to treatment with ozone at 13.9 mg/l 1 (6,482 ppm) and found that the egg mortality reached 62.5% at 2-h exposure time. Keivanloo et al (2014) stated that treatment with ozone resulted in 56.6% egg mortality of Plodia interpunctella (Hübner) at 5 ppm. In contrary with our results, Bonjour et al (2011) reported that treatment with ozone at a concentration of 70 ppm for 4 days did not cause signifi cant egg mortality of P. interpunctella.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Isikber and Oztekin (2009) investigated the susceptibility of Tribolium confusum Jacquelin du Val life stages to treatment with ozone at 13.9 mg/l 1 (6,482 ppm) and found that the egg mortality reached 62.5% at 2-h exposure time. Keivanloo et al (2014) stated that treatment with ozone resulted in 56.6% egg mortality of Plodia interpunctella (Hübner) at 5 ppm. In contrary with our results, Bonjour et al (2011) reported that treatment with ozone at a concentration of 70 ppm for 4 days did not cause signifi cant egg mortality of P. interpunctella.…”
Section: Discussionmentioning
confidence: 99%
“…resulted in 91% hatchability and 50% emergence respectively. Keivanloo et al, (2014) showed that not surprisingly, ozone had less effect on egg mortality of P. interpunctella. At the highest ozone concentration× exposure period treatment and the mortality of eggs were (56.66%).…”
Section: Effect Of Ozone Treatment On Eggs: Parental Generationmentioning
confidence: 96%
“…It is also used for the disinfection of specific equipment, devices, facilities, for cleaning ventilation and air conditioning. Ozone, as an oxidant, is widely used in water treatment and disinfection-it eliminates unpleasant odors, flavors, and colors [54,[60][61][62].…”
Section: Molecular Weightmentioning
confidence: 99%
“…Ozonation as a physical method is increasingly used in agriculture, horticulture, and their surroundings [62,66]. It is one of the most promising techniques in plant protection [67,68], it is more effective and acts more rapidly than other solutions used so far.…”
Section: Molecular Weightmentioning
confidence: 99%